Revised Ordinances of the City of Woburn, at 91 §§ 2-4 (1898) - (:unkn) unknown (General Publisher, 1898)
No person shall sell any gunpowder within the city, without such license. Every license shall be in force one year from the date thereof; provided, that any license may be rescinded by the City Council, at their discretion.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER